ANTIOXIDANT PROPERTY OF ANTIHYPERTENSIVE DRUGS (CARVEDILOL, ENALAPRIL, AND AMLODIPINE) ON LIVER FUNCTION IN ANIMAL (RATS) MODELS - Rajesh, Pusuloori (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: The antihypertensive drugs (beta-blockers - carvedilol, calcium channel blocker - amlodipine, and angiotensin-converting enzyme inhibitor - enalapril) were investigated for its hepatoprotective effect by antioxidant property against carbon tetrachloride (CCl )-induced acute liver damage on albino rats. Methods: In this study the liver was damaged by giving Carbon tetra chloride (CCl 4 )-1 ml/kg-p.o. After giving CCl (1 ml/kg), it significantly elevated the serum levels of biochemical markers such as serum glutamate-pyruvate transaminase, serum glutamic oxaloacetic transaminase, alkaline phosphatase, total bilirubin, protein, and depleted antioxidant enzymes glutathione. After treatment with carvedilol (10 mg/kg), enalapril (0.5 mg/kg), and amlodipine (10 mg/kg) for 2 weeks, these drugs were significantly reduces the elevated levels of biochemical markers mentioned above. Conclusion: These results suggest that these antihypertensive drugs may have the potential therapeutic value in the treatment of CCl 4 -induced hepatic damage and some liver diseases. Hepatoprotective activity of these drugs may be attributed to the antioxidant principles in it. Keywords: Antioxidant, Carvedilol, Enalapril, Amlodipine, Carbon tetrachloride, Hepatoprotective. 4 4